PENGARUH AMBIGUITAS PERAN, KONFLIK PERAN, DAN KEPATUHAN PADA KODE ETIK TERHADAP INDEPENDENSI APARAT PENGAWASAN INTERN PEMERINTAH - Sutaryo Sutaryo (Jurnal Ilmiah Wahana Akuntansi, 2017)
This research is conducted to find out empirical evidence of the effect of role ambiguity, role conflict, and code of ethics compliance on the state internal auditor to state internal auditor independence in Jawa Timur. This research, which uses quantitative approach, uses data sources by taking sample of 170 state internal auditors in Jawa Timur. The collected data is then analysed by multiple linear regression analysis mehtod. The result reveals that role ambiguity and role conflict have negative effect to the state internal auditor independence, however code of ethics compliance has positive effect to the state internal auditor independence. The higher the situation of ambiguity and role conflict preceived by APIP, it will further weaken its commitment to maintain independence in duty. But not so with compliance with the code of ethics, the higher the compliance of APIP to the code of ethics, it will further increase its commitment to maintain independence in the duty.